Pernikahan Dini Meningkatkan Risiko Kejadian Kanker Serviks - Kurniasari Pratiwi; Yuni Fitriana (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: The incidence and mortality from cervical cancer (cervical cancer) in theworld second only to breast cancer. Meanwhile, in developing countries still ranks asthe top cause of cancer deaths in the reproductive age. Cancer of the cervix is still athreat for women so it is called the "silent killer". Currently cervical cancer is still amatter of women's health should be taken seriously due to the high prevalence ofcervical cancer in Indonesia. Early marriage is one factor that is suspected to be thecause of the high prevalence of cervical cancer in Indonesia.Objective: This study aimed to determine whether there is a relationship between earlymarriage with the risk of cervical cancer.Methods: This study is a correlation study is to determine whether there is arelationship early marriage with risk of cervical cancer in the village Pandes, Wedi,Klaten, Central Java.Results and Conclusion: Based on the analysis of data analysis known p value of0.01 (p value <0.05), and is therefore interpreted the hypothesis is accepted that thereis a significant relationship between marriage themselves with the risk of cervicalcancer.Keywords: early marriage, cervical cancer